"A Cephalometrıc Analysıs Based On The True Vertıcal And The True Horızontal" - Emel Yücel Eroğlu (Galenos Yayinevi, 1992)
In the present study, a cephalometric analysis based on the true vertical and the true horizontal which were derived from lateral cephalometric radiographs taken in the "adjusted" natural head position, were developed. By means of this "new" analysis, the soft-tissue, skeletal and dental relationship of a "ideal" adult Turkish individuals were evaluated in order to establish cephalometric norms which were useful especially in the diagnosis and treatment planning of orthognathic surgery cases.